Skin Tuberculosis: A Case Report - Ahmad, Sami; Faruk, Imtiaz; Hussain, Md Margub; Faiz, MA (Journal of Bangladesh College of Physicians and Surgeons, 2010)
A 17 year old boy presented with multiple non healing ulcers over the right lower limb and left upper limb for 13 years which were non responsive to varieties of treatment modalities used in his locality. There were also contracture deformities of the affected limbs. Clinically the diagnosis was quite confusing. but histopathology of specimen from skin lesion confirmed it as a case of skin tuberculosis. The patient was put on anti TB drugs and the ulcers responded well and started to heal rapidly. Some reconstructive surgery will be done for his contractures after completion of the anti TB drug regimen and proper healing of ulcers. DOI: 10.3329/jbcps.v27i2.4255 J Bangladesh Coll Phys Surg 2009; 27: 107-111